2014
DOI: 10.1242/jcs.139865
|View full text |Cite
|
Sign up to set email alerts
|

Tead2 expression levels control Yap/Taz subcellular distribution, zyxin expression, and epithelial-mesenchymal transition

Abstract: The cellular changes during an epithelial-mesenchymal transition (EMT) largely rely on global changes in gene expression orchestrated by transcription factors. Tead transcription factors and their transcriptional co-activators Yap and Taz have been previously implicated in promoting an EMT; however, their direct transcriptional target genes and their functional role during EMT have remained elusive. We have uncovered a previously unanticipated role of the transcription factor Tead2 during EMT. During EMT in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 75 publications
12
125
0
Order By: Relevance
“…5, B and C). Consistent with our findings, through ChIP sequencing, a recent study also suggests that TEAD2 can regulate EMT-relevant genes by acting as a transcriptional activator or repressor mainly by directly binding to the promoters containing TREs (56). It is still unclear why the same TAZ-TEAD complex activates transcription of some cellular genes such as CTGF and Cyr61 but suppresses transcription of other genes such as ⌬Np63.…”
Section: Taz Is a Dual Regulator Of Gene Transcription-studies Havesupporting
confidence: 89%
“…5, B and C). Consistent with our findings, through ChIP sequencing, a recent study also suggests that TEAD2 can regulate EMT-relevant genes by acting as a transcriptional activator or repressor mainly by directly binding to the promoters containing TREs (56). It is still unclear why the same TAZ-TEAD complex activates transcription of some cellular genes such as CTGF and Cyr61 but suppresses transcription of other genes such as ⌬Np63.…”
Section: Taz Is a Dual Regulator Of Gene Transcription-studies Havesupporting
confidence: 89%
“…1B,D). In Tead cells, Yap showed stronger nuclear localization than in control GFP-expressing cells in single cultures , as has been shown for epithelial cells (Diepenbruck et al, 2014). In co-cultures, Tead cells also showed significantly stronger nuclear Yap signals than co-cultured normal cells (Fig.…”
Section: Tead2-overexpressing Cells Become Winners Without Causing Ovsupporting
confidence: 74%
“…Cross-linked chromatin (10 mg) was immunoprecipitated overnight at 4˚C with 2 mg of antiTead1 mouse monoclonal antibody (H-4, Santa Cruz Biotechnology) or anti-Yap1 mouse monoclonal antibody (Abnova) or normal mouse IgG (Santa Cruz Biotechnology). Quantitative PCR was performed using the following primer sets: Myc site 1-2, 59-GCGTTGGAAACCCCGGT-AAG-39 and 59-AGTCGCTCTACCCCGACTCA-39; Myc site 3, 59-ATCTGAGTCGGGGTAGAGCGA-39 and 59-GGGTCAGCGTCAGCC-CATAG-39; Myc site 4, 59-TTTTGAAGCGGGGTTCCCGA-39 and 59-GAAGCGACCTCCCGGTTTGA-39; Myc site 5-6, 59-ATGTTGGGCT-AGCGCAGTGA-39 and 59-CGGAACCGCTCAGATCACGA-39; Myc site 7, 59-AGTCCGACGAGCGTCACTGA-39 and 59-ACCACTCCC-CTTTCAGCGTG-39; Cyr61, 59-CTCTGATGGATCTGAGAAGAGG-39 and 59-GCCCTTTATAATGCCTGCCTA-39 (Diepenbruck et al, 2014); and Intergenic region, 59-GCTCCGGGTCCTATTCTTGT-39 and 59-TCTTGGTTTCCAGGAGATGC-39 (Diepenbruck et al, 2014). The fold enrichment was calculated using the 22DDCt method: 22[(Ct ChIP -Ct input) 2 (Ct IgG2 Ct input)], where Ct is the threshold cycle.…”
Section: Chip Assaymentioning
confidence: 99%
“…For instance, it has been demonstrated that TAZ is implicated in promoting migration and invasion in breast cancer cell models, 15 and it has also been shown that TAZ knockdown provokes defects in the maintenance of pluripotency in embryonic stem cells. 34 Hence, it would appear that TAZ is a potent activator of cell transformation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Dysregulation of the Hippo pathway is correlated with epithelial to mesenchymal transition and cancer development, mainly driven by TAZ and YAP. 15 These two DNA-binding proteins are normally repressed by Mst2 and Lats2 phosphorylation, 16,17 or they are regulated by the expression and location of the cell polarity protein Scribble. 18 TAZ/YAP and epithelial to mesenchymal transition are thought to maintain a bidirectional relationship, whereby the loss of polarity and cell contacts (key events during the epithelial to mesenchymal transition process) induces the activation of both factors, which in turn participate in the epithelial to mesenchymal transition program.…”
mentioning
confidence: 99%